Enhancing Students’ Comprehension of Comparisons of Trigonometric Functions through Remedial Learning Videos - Muslim, Imam; Mailizar, Mailizar; Elizar, Elizar (Universitas Sarjanawiyata Tamansiswa, 2025)
Students' failure to grasp mathematical concepts can impede their mastery of learning standards, necessitating remedial efforts often constrained by time. Video-based remedial learning emerges as an innovative solution to enhance learning effectiveness. This study assessed the improvement in student outcomes following video-based remedial learning. Using an experimental pretest-posttest design, the study involved 100 Year 11 and 12 students from a public high school in Sukamakmur, Aceh Besar, Indonesia. Data analysis, via N-Gain score and t-tests, revealed three key findings: (1) a notable improvement in student outcomes after video-based remedial learning on trigonometric comparisons, (2) a greater enhancement in science classes compared to social studies classes, and (3) a higher increase in Year 12 compared to Year 11. The results affirm that video-based remedial learning positively impacts students' understanding of trigonometric functions